Quality Assessment of Cervical Cytology Practices in Estonia From 2007 to 2018. (17th November 2022) - Orumaa, Madleen; Innos, Kaire; Suurna, Maria; Salumäe, Liis; Veerus, Piret
Background: Cervical cancer incidence and mortality in Estonia are among the highest in Europe, although the overall coverage with cervical cytology is high. This indicates potential issues with the quality of collection and/or laboratory evaluation of cervical cytology. Objectives: The aim of the retrospective observational study was to assess the quality of cervical cytology specimen collection, evaluation, and reporting using laboratory reports in Estonia. Methods: The study included women with a cervical cancer diagnosis in 2017−2018. Cervical cytology and histology reports for these women in 2007−2018 were obtained from ten laboratories. We described the quality of cytology specimen collection and reporting of cytology results. Multivariate logistic regression was used to calculate odds ratios (OR) with 95% confidence intervals (CI) to identify factors associated with NILM as the last cervical cytology result within 5 or 2 years before the cervical cancer diagnosis. Also, we calculated cytology-histology correlation (CHC). Results: We identified 503 cytology and 100 histology reports from 138 women. The laboratories differed greatly regarding human resources, work capacity and volume. Differences between local and regional laboratories were observed in reporting specimen adequacy (P < .001). We found that local laboratories had 3 times higher odds (OR = 2.95, 95% CI: 1.05−8.33) of reporting normal results 2 years before cancer diagnosis than regional laboratories. According to the CHC, 58.9% of pairs were in agreement. Conclusions: The study showed considerable heterogeneity and suboptimal performance of cervical cytology practices in Estonia, particularly at local laboratories. Efforts to improve laboratory quality assurance are crucial.